2008
DOI: 10.1007/s11864-008-0058-0
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Pediatric Hodgkin Lymphoma

Abstract: We are increasingly successful in the treatment of Hodgkin lymphoma. Current risk adapted trials seek to maintain the excellent efficacy of older therapies, while simultaneously limiting their late toxicities. Current management of early stage/favorable disease involves the use of two to four cycles of tailored chemotherapy, often followed by low-dose, involved field radiation. Those with intermediate and advanced stage disease require more intense chemotherapy and radiation regimens. Functional imaging using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…Several investigators have reported the efficacy of auBMT for most patients with rrHL [6,[10][11][12]22]. Although direct clinical trial comparison data are lacking, the collective experience is that outcomes for patients with rrHL are best if these patients undergo auBMT as opposed to non-auBMT regimens [6][7][8]10]. For example, in 1 study of adult patients that directly compared salvage chemotherapy to high-dose chemotherapy with auBMT, those who received auBMT had an EFS almost twice as high as those that did not receive auBMT (53% compared with 27%) and also had increased OS (54% compared with 47%) [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several investigators have reported the efficacy of auBMT for most patients with rrHL [6,[10][11][12]22]. Although direct clinical trial comparison data are lacking, the collective experience is that outcomes for patients with rrHL are best if these patients undergo auBMT as opposed to non-auBMT regimens [6][7][8]10]. For example, in 1 study of adult patients that directly compared salvage chemotherapy to high-dose chemotherapy with auBMT, those who received auBMT had an EFS almost twice as high as those that did not receive auBMT (53% compared with 27%) and also had increased OS (54% compared with 47%) [5].…”
Section: Discussionmentioning
confidence: 99%
“…Attempts to cure children with incompletely responsive or rapidly relapsed disease (recurrence 12 months from end of therapy) with salvage chemotherapy strategies that do not include auBMT have been less successful, with reported overall survival (OS) as low as 47% and event-free survival (EFS) as low as 27% [5]. High-dose chemotherapy followed by auBMT is effective therapy for patients with relapsed or refractory HL (rrHL) and has become a standard approach for such patients, with OS ranging from 43% to 95% [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…2 However, long term effects of therapy have prompted several groups to attempt reduction of therapy, particularly in children with low risk HL. These attempts have varied in their approach, including elimination of radiation therapy 16 , the use of non-alkylator chemotherapy, 4, 5 or response based reduction of chemotherapy and/or radiation therapy.…”
Section: Discussionmentioning
confidence: 99%
“…1 The therapy for lower risk patients, Ann Arbor Stages I, IIA and IIIA 1 is very effective with event free survivals and overall survivals greater than 90% 2, 3 . Although intensive combined modality chemotherapy and radiation therapy regimens have achieved excellent results, concern over short and long-term side-effects are substantial and many groups are currently evaluating reduced forms of therapy 48 .…”
Section: Introductionmentioning
confidence: 99%
“…Recurring somatic mutations in these genes are not known to occur in the pediatric solid tumor or ALL setting. Among the lymphomas known to show NF-κB activation in the adult setting, Hodgkin lymphoma and primary mediastinal B-cell lymphoma occur in the pediatric age range [31,32]. Further preclinical evaluations of MLN4924 will depend upon emerging data from adult preclinical and clinical testing and on future advances in the understanding of the molecular basis of pediatric cancers.…”
Section: Discussionmentioning
confidence: 99%